Design and implementation of solar-grid based charging station for electric vehicle with fault detection method using R-Pi and IoT processor - Vaigundamoorthi, M.; Karthick, S.; Chandrika, V. S.; Chithra, D.; Balaramakrishna, K. V.; Khandan, K. Lakshmi; Maguluri, Lakshmana Phaneendra; Chandrasekar, S.; Janarthanan, M. (International Journal of Applied Power Engineering (IJAPE), 2025)
In this research describes the electrical vehicle (EV) charging station using PV panel with fault detection methods. The PV modules will failure for some time, because of some external factors and internal factors. In direct fault condition the monitor and analyze the external factors such as the life span, high intensity and breakage of the PV panels using Raspberry Pi (R-Pi) processor with internet of things (IoT) system. In power demand/day on the PV panel will be evaluated and analyzed through R-Pi processor and IoT. The efficiency and the range values of the PV panels will be monitored and analyzed through IoT. Proposed work explains, how the fault detection techniques have been improved and adopted in using R-Pi processor through IoT platform. The proposed dataset pre-processing system is incorporated with IoT module. The grid fault clearing time will be compared with the actual values through R-Pi processor. The PV panel faults are detected using thermal image processing, that image parameter values analysis through IoT based internal monitoring system.